The effects of traveling in different transport modes on galvanic skin response (GSR) as a measure of stress: An observational study. (November 2021) - Yang, Xiuleng; McCoy, Emma; Anaya-Boig, Esther; Avila-Palencia, Ione; Brand, Christian; Carrasco-Turigas, Glòria; Dons, Evi; Gerike, Regine; Goetschi, Thomas; Nieuwenhuijsen, Mark; Pablo Orjuela, Juan; Int Panis, Luc; et al.
Highlights: Galvanic skin response (GSR) measurements are used as a proxy measure of stress. Propensity score matching and linear mixed models are used to examine effects of travel modes on GSR. Cycling reduces GSR by up to 11% compared to other non-cycling activities. Walking reduces GSR by up to 6% compared to other non-walking activities. Motorized travel increases GSR by up to 1% compared to any other activities than motorized travel. Abstract: Background: Stress is one of many ailments associated with urban living, with daily travel a potential major source. Active travel, nevertheless, has been associated with lower levels of stress compared to other modes. Earlier work has relied on self-reported measures of stress, and on study designs that limit our ability to establish causation. Objectives: To evaluate effects of daily travel in different modes on an objective proxy measure of stress, the galvanic skin response (GSR). Methods: We collected data from 122 participants across 3 European cities as part of the Physical Activity through Sustainable Transport Approaches (PASTA) study, including: GSR measured every minute alongside confounders (physical activity, near-body temperature) during three separate weeks covering 3 seasons; sociodemographic and travel information through questionnaires. Causal relationships between travel in different modes (the "treatment") and stress were established by using a propensity score matching (PSM) approach to adjust for potential confounding and estimating linear mixed models (LMM) with individuals as random effects to account for repeated measurements. In three separate analyses, we compared GSR while cycling to not cycling, then walking to not walking then motorized (public or private) travel to any activity other than motorized travel. Results: Depending on LMM formulations used, cycling reduces 1-minute GSR by 5.7% [95% CI: 2.0–16.9%] to 11.1% [95% CI: 5.0–24.4%] compared to any other activity. Repeating the analysis for other modes we find that: walking is also beneficial, reducing GSR by 3.9% [95% CI: 1.4–10.7%] to 5.7% [95% CI: 2.6–12.3%] compared to any other activity; motorized mode (private or public) in reverse increases GSR by up to 1.1% [95% CI: 0.5–2.9%]. Discussion: Active travel offers a welcome way to reduce stress in urban dwellers' daily lives. Stress can be added to the growing number of evidence-based reasons for promoting active travel in cities.